POSTPARTUM REHABILITATION OF PATIENTS WHO HAVE PERFORMED LATTER-SAVING OPERATIONS: METRORAPHY AND METROPLASTICS - Umarova , N.M.; Nigmatova , G.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
According to the results of the III confidential analysis of maternal mortality (MS) cases for 2016-2017. (KISMIS) "In the name of saving mothers’ lives," the cause of MS from genital sepsis was 14.7%, and according to various authors, the incidence of purulent-septic complications of the postpartum period varies from 1 to 54.38%. Postpartum women who have undergone complicated surgical deliveries through cesarean section, uterus-preserving reconstructive surgeries (metroraphy and metroplasty), allow for the preservation of quality of life, especially for first-time mothers, as it prevents the development of a number of complications associated with the removal of the uterine organ, which is not only a childbearing organ but also participates in the process of hormonal regulation in women.